Enredos de resistência da família Paiva : violência política, solidariedade e afetuosidade (1971 – 2015) - Teodózio, Ana Cristina (2020)
More than forty years after the disappearance of his father, imprisoned, tortured and murdered by the Brazilian civil-military dictatorship, writer Marcelo Rubens Paiva returned with his memorial writing when he launched the novel "I am still here". The work tells his family history, centred on his mother, Eunice Paiva, and leaves as a legacy the trauma of his father's death to the readers of his memoirs. Thus, autobiographical and published in 2015, it was a denunciation of dictatorial oppression and became a weapon in the fight against the forgetfulness of the death and political disappearance of the former federal deputy, Rubens Beyrodt Paiva. Analyzing this work consisted in recovering the memory of one of the most tense periods in the history of Brazil, as well as leaving alive the memory of disrespect for human rights. The interpretative basis with which this research was worked was that the writing of the memory employed by this author assumed a social and moral function. Social, as it provides subsidies for clarifying and understanding the facts of a certain historical period from a crucial point - the disappearance of his father - as opposed to the official version. And moral, by performing what is understood as accountability with one's own conscience, with the actions taken by him and his family before the anti-dictatorial posture assumed. The research aimed, thus, to understand the history of struggle and resistance of this family that suffered the political violence impetrated by the dictatorial regime, and to discuss the use of autobiography as a place of memory, resistance and denunciation. It also sought to analyze the public policies of memory and reparation for the crimes of the Brazilian dictatorship, using as a source for the development of its ideas, the autobiographical writings Still here (2015) and Happy Old Year (1982), by writer Marcelo Rubens Paiva, the biography of Rubens Paiva (2013) written by Jason Tércio, written and spoken interviews, newspaper articles, copies of court cases and a report of the Truth Commission of Rio (CEV-Rio).